Elevated Mercury Concentrations in Humans of Madre de Dios, Peru - Ashe, Katy (Public Library of Science, 2012)
The enormous increase in practically unregulated mining in Madre de Dios Peru is leading to massive release of liquid elemental mercury to the environment. Rapidly increasing global prices for gold are causing a massive upsurge in artisanal mining in the Peruvian Amazon, considered to be one of the most biodiverse places on the planet. This study identifies the current levels of mercury in the human population, through identifying levels of total mercury in human hair in mining zones of Madre de Dios Department and in the nearby city of Puerto Maldonado. A regression analysis reveals that fish consumption, gender, and location of residence were significant indicators of mercury levels; while duration of residence and age had no significant relationship to mercury levels. Increased fish consumption levels were the strongest indicators of increased total mercury levels across the entire population. The levels of total mercury in hair was significantly (α = 0.05) higher in mining zones, than Puerto Maldonado. In both areas men had significantly higher levels than women, likely due to a difference in metabolism or varying levels of direct involvement in gold mining- a male predominated industry. This is the first study to show the health threat that mercury poses to this region, however further research needs to be done to gain a more refined understanding of the predominant routes of exposure in this population.